Hubungan Beban Kerja dengan Penerapan Patient Safety pada Perawat Diruang Rawat Jalan - Ratih Ayu Ningsih; Inas Syabanasyah; Solehudin Solehudin (PPNI UNIMMAN, 2026)
Patient safety is one of the key elements in providing quality health services. Patient safety is a top priority because it has become a global issue in hospital health services. This study aims to determine the relationship between workload and the implementation of patient safety among nurses in the Outpatient Room of Grha Permata Ibu Hospital in 2025. This study is a quantitative, analytical study. This quantitative research uses a cross-sectional design. The population in this study consisted of 40 nurses in the Outpatient Room of Grha Permata Ibu Hospital. Therefore, the sample in this study consisted of 40 respondents using a total sample technique. The instrument used in this study was a questionnaire. Data analysis was performed using univariate and bivariate analysis with the chi-square test. Based on the statistical test results, the p-value was 0.023, meaning that p-value < α (0.05). Therefore, it can be concluded that there is a relationship between workload and the implementation of patient safety among nurses in the Outpatient Ward of Grha Permata Ibu Hospital in 2025. The hospital is advised to ensure fair task distribution, provide facilities, and offer training and psychological support to manage stress.